Faktor yang Berpengaruh terhadap Kegagalan Pengendalian Diabetes Melitus Tipe 2 pada Pasien yang Berobat di PT. Askes Cabang Sampit Kabupaten Kotawaringin Timur - Diana Diana; Heri Nugroho; Suharyo Hadisaputro (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2017)
Background: Diabetes mellitus is a chronic disease characterized by blood glucose levels than normal, impaired metabolism of carbohydrates, fats and proteins caused by a deﬁciency of the hormone insulin relative or absolute. Control of blood sugar in people with DMT 2 is an essential requirement for delaying complications, in the community. DMT 2 risk factor is age, long- suffering, sex, education, socio-economic, knowledge, attitudes, practices, patterns of diet, obesity, how to take medication, exercise, family support, educate physicians and nutritionists. The purpose ofthe study describes some of the factors that inﬂuence the DMT2 control failure.Methods: The study used a case-control design is reinforced by the qualitative study. The number of respondents was 122, including 61 cases and 61controls taken by consecutive sampling. Analysis ofthe data using univariate, bivariate (chi-square) and multivariate (logistic regression).Results: Analysis of some factors that inﬂuence the attitude control DMT 2 (OR 34.4), exercise (OR 8.7), knowledge (OR 8,4), age (OR 5.9), family support (OR 5.2), how totake medication (OR 3.5). Various factors were not shown to signiﬁcantly affect the failure to control type 2 diabetes mellitus are: Long suffering, sex, smoking, education, socio-economic, diet, obesity, stress/depression, education of physicians and nutritionists.Conclusion: Several factors were shown to inﬂuence the incidence of DMT 2 control attitude, exercise, knowledge, age, family support, and how to take the medicine.